2000
DOI: 10.4049/jimmunol.164.9.4689
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Inducible Costimulator Ligand Expression and Function

Abstract: The inducible costimulator (ICOS) is the newest member of the CD28/CD152 receptor family involved in regulating T cell activation. We constructed a soluble-Ig fusion protein of the extracellular domain of human ICOS and used it as a probe to characterize expression patterns of the ICOS ligand (ICOSL). ICOSIg did not bind to CD80- or CD86-transfected Chinese hamster ovary cell lines, demonstrating that ICOSL is distinct from those ligands identified for CD28/CD152. ICOSIg showed selective binding to monocytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(174 citation statements)
references
References 38 publications
(23 reference statements)
8
163
3
Order By: Relevance
“…1B). Although some suggest that ERK is activated downstream of CD40 in B cells (7), others have suggested that this may not be the case (4,5) or that CD40-induced ERK activation may be more prominent in monocytic cells than in B cells (51). Our results, based on early gene expression, agree with the latter hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…1B). Although some suggest that ERK is activated downstream of CD40 in B cells (7), others have suggested that this may not be the case (4,5) or that CD40-induced ERK activation may be more prominent in monocytic cells than in B cells (51). Our results, based on early gene expression, agree with the latter hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, there is evidence that PD-L1: PD-1 interactions may influence alloreactive T cell responses by inducing regulatory cells, and that blocking of PD-L1, but not PD-L2 signaling, prevents their induction (52). Interestingly, ICOSL expression, that was observed at comparatively low levels on both AADC and control GMDC in the present study, is not (unlike CD80 and CD86) dependent on NF-B activation (53).…”
Section: Discussionmentioning
confidence: 48%
“…This could suggest the convergence or competition of LIGHT and CD40L signaling for Ig secretion for a limiting step that, thus, could not be modified by additional stimulation. In addition to stimulation by TNF/TNFR family members, interaction of ICOS [4], which is a member of the B7 family of costimulatory molecules, with its ligand [5] has also an important role in B cell physiology. ICOS is expressed on both CD4 + and CD8 + activated T lymphocytes [6].…”
Section: Light Stimulation Enhances Ig Secretionmentioning
confidence: 99%